2014
DOI: 10.1063/1.4878411
|View full text |Cite
|
Sign up to set email alerts
|

Phase diagram of two-dimensional hard ellipses

Abstract: We report the phase diagram of two-dimensional hard ellipses as obtained from replica exchange Monte Carlo simulations. The replica exchange is implemented by expanding the isobaric ensemble in pressure. The phase diagram shows four regions: isotropic, nematic, plastic, and solid (letting aside the hexatic phase at the isotropic-plastic two-step transition [PRL 107, 155704 (2011)]). At low anisotropies, the isotropic fluid turns into a plastic phase which in turn yields a solid for increasing pressure (area fr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 47 publications
2
55
0
Order By: Relevance
“…[31][32][33][34][35][36] The studies show there are differences between the nature of 2D nematic ordering and 3D one. So, we examined the orientation ordering properties of 2D hard ellipsoids.…”
Section: Resultsmentioning
confidence: 99%
“…[31][32][33][34][35][36] The studies show there are differences between the nature of 2D nematic ordering and 3D one. So, we examined the orientation ordering properties of 2D hard ellipsoids.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, this study did not demonstrate the formation of a disordered glass under slow near-equilibrium compression. Simulations show that hard, elongated ellipses having aspect ratios (i.e., semimajor axis divided by semiminor axis) greater than 2.4 form nematic phases (25). In the limit of very high aspect ratios, dispersions of rod-like fd virus, when slowly compressed, have yielded liquid crystals that possess long-range orientational order and are therefore not glasses (26).…”
mentioning
confidence: 99%
“…(The formation of a nematic crystal may be avoided for larger systems since the nematic order parameter is expected to decrease with the system size. 36 For instance, the replica exchange MC simulations 36 indicate that an isotropic-plastic transition occurs for monodisperse hard ellipses with aspect ratios up to k ≃ 1.6, while a nematic liquid crystal forms at sufficiently high densities when k ≥ 2.4. 34,35 Instead, we have found that a binary hard-ellipse system with an aspect ratio of around k = 2 exhibits characteristic glassy dynamics on increasing density for the chosen size disparities both translationally and rotationally.…”
Section: Model and Simulation Detailsmentioning
confidence: 99%